The Usability of Hip Protectors: A Mixed-Method Study from the Perspectives of Singapore Nursing Home Care Staff - Tianma Xu; Yu Venedict Lim; Lynn Shi Xuan Wee; Yong Jean Shina Tan; Agnes Lishan Xue (Journal of Ageing and Longevity)
The EXO+ hip protector was developed to minimize the risk of hip fractures in seniors following falls. This study evaluated its usability in a Singapore nursing home from the perspective of the staff, focusing on learnability, efficiency, and satisfaction. A mixed-method design was employed, with nursing home residents wearing the EXO+ daily for eight weeks. Quantitative data on wear time were collected alongside qualitative insights from four repeated focus group discussions with care staff. In total, 15 residents (including 8 residents with cognitive impairments) and 9 staff participated. The analysis revealed six themes and fourteen subthemes related to EXO+’s usability. The residents wore the device for an average of 1.54 h per day, with those having cognitive impairments showing increased wear times, especially in the mornings and on weekdays. The findings indicated that the EXO+ was learnable and satisfactory for nursing home use, provided there are adequate supporting features. The efficiency of the EXO+ was not fully measured since no falls were reported during the study period. The study offers valuable insights for potential design modifications and workflow adaptations to enhance the implementation of hip protectors in healthcare settings, highlighting facilitators and barriers to support device uptake.